2017
DOI: 10.1111/nyas.13363
|View full text |Cite
|
Sign up to set email alerts
|

A cCPE‐based xenon biosensor for magnetic resonance imaging of claudin‐expressing cells

Abstract: The majority of malignant tumors originate from epithelial cells, and many of them are characterized by an overexpression of claudins (Cldns) and their mislocalization out of tight junctions. We utilized the C-terminal claudin-binding domain of Clostridium perfringens enterotoxin (cCPE), with its high affinity to specific members of the claudin family, as the targeting unit for a claudin-sensitive cancer biosensor. To overcome the poor sensitivity of conventional relaxivity-based magnetic resonance imaging (MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 69 publications
(165 reference statements)
0
17
0
Order By: Relevance
“…A unique peak for Xe@CryA, i.e., in a lipidic/cellular environment (~120 ppm) could be observed. Thus, this approach demonstrated that a significantly lower expressed cellular target can be efficiently detected using the highly sensitive HyperCEST method while such targets normally remain inaccessible to relaxivity-based MR agents [ 194 ].…”
Section: Aspects Of 129 Xe Biosensor Designmentioning
confidence: 99%
See 1 more Smart Citation
“…A unique peak for Xe@CryA, i.e., in a lipidic/cellular environment (~120 ppm) could be observed. Thus, this approach demonstrated that a significantly lower expressed cellular target can be efficiently detected using the highly sensitive HyperCEST method while such targets normally remain inaccessible to relaxivity-based MR agents [ 194 ].…”
Section: Aspects Of 129 Xe Biosensor Designmentioning
confidence: 99%
“…As many dyes are commercially available in a biotinylated form (e.g., a FITC-biotin conjugate) a modular biosensor approach allows to couple both CryA-biotin and FITC-biotin to an avidin-labeled targeting unit. This has been demonstrated for the CD14-targeted sensor [ 15 ] and the claudin-4-directed one [ 194 ]. Besides such building blocks relying on avidin coupling units, it is also possible to synthesize CryA-dye conjugates with a -COOH handle for further coupling [ 234 ].…”
Section: Aspects Of 129 Xe Biosensor Designmentioning
confidence: 99%
“…These xenon–host ensembles, termed biosensors, currently come in two major classes: supramolecular compounds such as conjugates of cryptophanes, cyclodextrins, pillar[5]arenes, cucurbiturils, and metal‐organic frameworks and larger compartmental carriers including viral capsids, gas vesicles, and liposomes . The ever‐expanding array of xenon biosensors has been applied to the selective detection of a variety of binding events involving metal ions, receptors on cell surfaces, transmembrane proteins, enzymes, biothiols, and reporting on microenvironments indicative of tumors, such as abnormal pH, specific ionic milieus or oxidation …”
Section: Figurementioning
confidence: 99%
“…[8][9][10][11][12][13] The ever-expanding array of xenonb iosensors has been applied to the selective detection of av ariety of binding eventsi nvolving metal ions, receptors on cell surfaces, transmembrane proteins, enzymes, biothiols, and reporting on microenvironments indicative of tumors,s uch as abnormal pH, specific ionic milieus or oxidation. [9,10,[13][14][15][16][17][18][19][20][21][22][23][24] Cucurbit[n]urils (CBns) comprise ac lass of hosts for 129 Xe hy-perCESTa pplications, which are useful because of their commerciala vailability and favorable xenon exchange kinetics. [25] CBns are donut-shaped molecules comprised of n glycoluril units linked by methylene bridges (Figure 1a,C B7 shown) that can form dynamic host-guest complexes with av ariety of moieties.…”
mentioning
confidence: 99%
“…Using a cw radio frequency pulse over several seconds, cucurbit[6]uril (CB6) as the host enables a very efficient saturation transfer due to its chemical exchange rates of k BA ~2,100 s −1 into the pool of free Xe in aqueous environment . To allow for the observation of highly dilute concentrations of bound 129 Xe, the method combines spin hyperpolarization and CEST (Hyper‐CEST) that has already been applied for various other molecular sensing applications . Addition of the enzyme for substrate conversion into the product with its high host affinity displaces Xe from the host and thus reduces the Hyper‐CEST response, that is, prevents the saturation transfer onto dissolved Xe.…”
Section: Introductionmentioning
confidence: 99%